INDIKATOR-INDIKATOR YANG MEMPENGARUHI STRES KERJA TERHADAP KESELAMATAN DAN KESEHATAN KERJA (K3) - AYU WULANDARI (Program Studi Teknik Sipil Universitas Narotama, 2022)
Work stress is the main indication that results in physical and mental disruption of every human being, which results in affecting Occupational Health and safety (K3). Occupational Safety and health (K3) is one of the most important aspects in the implementation of a construction project, it is because a construction project involves a wide range of resources. The purpose of the study was to identify factors that influence occupational stress on Occupational Health and safety (K3). This research method is a literature study by examining several journals related to the relationship of work stress with Occupational Health and safety (K3). Data collection techniques by collecting several previous studies to identify what factors cause occupational stress on Occupational Health and safety (K3). The data obtained were analyzed using index and variance values (to determine the ranking of each factor). The results of understanding several journals related to the relationship of stress with Occupational Health and safety (K3) showed that the factors were short time targets, too many jobs, large levels of difficulty, high work pressure, work environment conflicts, unclear instructions, communication errors, unfair treatment, inappropriate salaries, feelings of boredom and boredom, work environment discomfort, family environment conflicts.